2003
DOI: 10.1161/01.cir.0000066697.19571.af
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Upregulates Gene Expression of Endothelial Nitric Oxide Synthase in Human Vascular Endothelial Cells

Abstract: Background-Histamine has a short-term, transient, stimulating effect on endothelial nitric oxide synthase (eNOS) activity; however, long-term effects on eNOS have not been described yet. In addition, the vascular effect of histamine seems to depend critically on eNOS functionality. Therefore, we studied the effects of histamine on eNOS gene expression and function. Methods and Results-In human umbilical vein endothelial cells (HUVECs) and HUVEC-derived EA.hy 926 cells, histamine upregulated eNOS mRNA (RNase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 36 publications
4
62
1
4
Order By: Relevance
“…Although both the H1 and H2 histamine receptors are reportedly expressed in endothelial cells (5,19), our data indicate that the H1 receptor, but not the H2 receptor, mediates the histamine signal leading to Egr-1 expression. Related to our finding, previous studies have shown that histamine-induced expression of p-selectin (9), ICAM1, VCAM1 (10), IL6, IL8 (8), cyclooxygenase-2 (27), and tissue factor (11) is mediated by the H1 receptor in vascular endothelial cells.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Although both the H1 and H2 histamine receptors are reportedly expressed in endothelial cells (5,19), our data indicate that the H1 receptor, but not the H2 receptor, mediates the histamine signal leading to Egr-1 expression. Related to our finding, previous studies have shown that histamine-induced expression of p-selectin (9), ICAM1, VCAM1 (10), IL6, IL8 (8), cyclooxygenase-2 (27), and tissue factor (11) is mediated by the H1 receptor in vascular endothelial cells.…”
Section: Discussioncontrasting
confidence: 54%
“…An early study indicates that H1 receptor is expressed in human endothelial cells (5), and a recent report suggests that histamine receptor 2 (H2) is also expressed in human endothelial cells (19). To determine which of the receptors indeed mediates histamine-induced Egr-1 expression in HAECs, we pretreated HAECs with one of the H1 receptor-specific antagonists, either mepyramine or chlorpheniramine, or with the H2 receptor-specific antagonist cimetidine for 40 min.…”
Section: Histamine Induction Of Egr-1 Expression Is Dependent On the H1mentioning
confidence: 99%
“…Further evidence to support the role of the NO-cGMP pathway in anaphylaxis is demonstrated by the finding that increased histamine results in upregulation of eNOS gene expression with increased production of NO leading to vasodilation through increased activity of GC. Inhibition of GC reduces vasodilation induced by histamine [53][54][55]. This evidence provides support that histamine-induced vasodilation is at least partly mediated through the NO-cGMP pathway and that inhibition of this pathway reverses the vasodilation.…”
Section: The No-cgmp Pathway In Anaphylaxis and The Role Of Methylenesupporting
confidence: 55%
“…Intracellular ROS Production-Intracellular ROS production by human RPE cells in response to TNF-α, IL-1β, or IFN-γ treatment was measured by a cell-based fluorometric assay based on deacetylation and oxidation of non-fluorescent reduced CM-H 2 DCFDA (Molecular Probes) into fluorescent CM-DCF. The reliability and specificity of the probe have been established in various cells including cultured human RPE cells (Deshpande et al, 2000;Nishikawa et al, 2000;Touyz et al, 2001;Yamagishi et al, 2001;Higgins et al, 2003;Li et al, 2003;Fukami et al, 2004;Hermann et al, 2004;Hwang et al, 2004;Kannan et al, 2004;Shanker et al, 2004;Kim et al, 2005). RPE cells were seeded into 96-well plates pre-coated with poly-D-lysine (Sigma-Aldrich) and cultured for 1 day or 7days.…”
Section: Measurement Of Reactive Oxygen Species Production By Rpe Cellsmentioning
confidence: 99%